Occurrence of caffeine in wastewater and sewage and applied techniques for analysis: a review - Marasco Júnior, César Augusto; Luchiari, Natália da Costa; Lima Gomes, Paulo Clairmont Feitosa (Eclética Química, 2019)
Emerging contaminants are substances found in the environment whose concentrations vary from µg to ng L-1 and whose presence in wastewater has gained popularity in the scientific community due to the potential impacts these compounds can cause to the environment. This designation concerns the lack of legislation to regulate their discharge or even to monitor these compounds. Moreover, emerging contaminants are capable of causing harmful effects to nontarget organisms and therefore affect the ecosystem balance. There are several compounds classified as emerging contaminants such as pharmaceuticals, illicit drugs, hormones, pesticides, among others. And among them, caffeine is considered an emerging contaminant and can be highlighted due its presence in medicines, beverages, foodstuff and several other products. In addition, it is a compound used worldwide recognized as a marker of anthropogenic activity. In this review, we present a discussion about emerging contaminants, focusing on caffeine, regulatory aspects that involve the theme, as well as effects on organisms, removal technologies and techniques for analyzing these compounds in environmental matrices.